A checklist of Bombyliidae (Diptera) from Mordovia, Russia and variation of wing shape in Bombylius species - MARIYA ALEXANDROVNA CHURSINA; ALEXANDER BORISOVICH RUCHIN (Society for Indonesian Biodiversity, 2018)
Chursina MA, Ruchin AB. 2018. A checklist of Bombyliidae (Diptera) from Mordovia, Russia and variation of wing shape in Bombylius species. Biodiversitas 19: 2147-2156. A checklist of Bombyliidae (Diptera) of Republic of Mordovia (Russia) is provided, based on material collected from 2008 to 2017. One hundred ninety specimens from 75 localities were collected. Fourteen of the twenty species are listed as belonging to the fauna for the first time. Intraspecific variation and sexual dimorphism in the wing shape of three species of the genus Bombylius Linnaeus, 1758 were investigated using geometric morphometric techniques. The analysis revealed that wing shape is a good discriminator of the species. In addition, significant sexual dimorphism were found: females of two of the three species had larger wings than males. The sex shape differences consisted mainly of ?hanges in the placement of the CuA and A1, while interspecific wing shape variation distributed in more dimensions. There was no evidence for allometric relationships relating to sexual dimorphism and interspecific variation. Potential adaptive significance of interspecific and intersex variation in wing size and shape is discussed.